PERPUTARAN MODAL KERJA, LIKUIDITAS DAN SOLVABILITAS DALAM MENINGKATKAN PROFITABILITAS PERUSAHAAN - EDWIN AGUS BUNIARTO (AKADEMIKA, 2022)
This study aims to determine the effect of working capital turnover, liquidity and solvency on profitability in food and beverage sub-sector companies in the Indonesian Capital Market for the 2016-2020 period. Working capital turnover is calculated using the Working Capital Turnover ratio, liquidity is measured using the Current Ratio, solvency is measured using the Debt to Assets Ratio and Profitability is measured using Return on Assets. This type of research is quantitative using multiple linear regression analysis. The sampling technique used purposive sampling method. The results of the analysis show that working capital turnover, liquidity and solvency have a significant effect on company profitability. This is evidenced by the results of correlation analysis which shows the value of r2 = 0.831, which means that there is an influence between working capital turnover, liquidity and solvency on profitability. Partially, each independent variable has a significant effect on profitability.